Say What You Say (Eminem): Managing Verbal Boundaries when using Rap in Music Therapy, a Qualitative Study - Short, Helen (Voices: A World Forum for Music Therapy, 2013)
This study identifies and describes considerations for managing verbal boundaries and the potential contraindication when using Rap in music therapy. The literature review covers the small number of case studies documenting the use of Rap in music therapy. The method used was an in-depth qualitative interview of 8 music therapy experts from a range of countries and approaches, experienced in the use of Rap as an intervention. A combination of grounded theory and thematic analysis was used to analyse data. The results are placed in context of the literature review and draw upon a number of psychodynamic concepts in order to determine a set of themes that could further inform those music therapists using Rap as a clinical intervention. The results display the flexibility with which Rap can be used to meet different levels of client need and how therapists' boundary management allows this. The data contributes towards clarifying what informs music therapists when considering how to manage the potentially offensive material that may be introduced into the therapy space when using Rap and when it may contraindicate. The research could serve as a preparatory tool for those therapists new to the genre and its use within therapy.